2017
DOI: 10.1111/ctr.12941
|View full text |Cite
|
Sign up to set email alerts
|

Ledipasvir/sofosbuvir is effective and well tolerated in postkidney transplant patients with chronic hepatitis C virus

Abstract: Patients with end-stage renal diseases on hemodialysis have a high prevalence of hepatitis C infection (HCV). In most patients, treatment for HCV is delayed until postrenal transplant. We assessed the effectiveness and tolerance of ledipasvir/sofosbuvir (LDV/SOF) in 32 postkidney transplant patients infected with HCV. The group was composed predominantly of treatment-naïve (75%) African American (68.75%) males (75%) infected with genotype 1a (62.5%). Most patients received a deceased donor kidney graft (78.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…There is increasing data that DAAs can be successfully used in kidney transplant recipients with low rates of adverse events and without increasing the rate of acute rejection (Table and S1). Results from 2 prospective clinical trials and 10 retrospective series of kidney transplant recipients demonstrated that more than 97% were cured with DAAs and the rate of acute rejection was less than 2% . It is important to note that nearly one‐third needed adjustment in calcineurin inhibitor dose during or shortly after stopping DAA therapy, suggesting extremely close monitoring of calcineurin inhibitor levels is needed, particularly if treatment is occurring in the early post‐transplant period.…”
Section: Treating Hcv With Direct‐acting Antiviral Therapies After Kimentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing data that DAAs can be successfully used in kidney transplant recipients with low rates of adverse events and without increasing the rate of acute rejection (Table and S1). Results from 2 prospective clinical trials and 10 retrospective series of kidney transplant recipients demonstrated that more than 97% were cured with DAAs and the rate of acute rejection was less than 2% . It is important to note that nearly one‐third needed adjustment in calcineurin inhibitor dose during or shortly after stopping DAA therapy, suggesting extremely close monitoring of calcineurin inhibitor levels is needed, particularly if treatment is occurring in the early post‐transplant period.…”
Section: Treating Hcv With Direct‐acting Antiviral Therapies After Kimentioning
confidence: 99%
“…Results from 2 prospective clinical trials and 10 retrospective series of kidney transplant recipients demonstrated that more than 97% were cured with DAAs and the rate of acute rejection was less than 2%. 9,23,[26][27][28][29][30][31][32][33][34][35] It is important to note that nearly one-third needed adjustment in calcineurin inhibitor dose during or shortly after stopping DAA therapy, suggesting extremely close monitoring of calcineurin inhibitor levels is needed, particularly if treatment is occurring in the early post-transplant period.…”
Section: Treating Hcv With Direct-acting Antiviral Therapies After Kimentioning
confidence: 99%
“…There are 3 prospective trials involving DAAs in kidney transplant recipients and several retrospective studies documenting the efficacy of therapy in these patients. These studies are reviewed in Table and we emphasize a few important trials with each of the major regimens …”
Section: Daas In Kidney Transplant Recipients: Current Experience Andmentioning
confidence: 99%
“…In addition to the above prospective trials, several centers have retrospective experience with DAAs with a total of ∼321 liver and renal transplant recipients (see Table ) . The majority of patients received sofosbuvir regimens several months to years posttransplantation with an eGFR >30 mL/min/1.73 m 2 .…”
Section: Daas In Kidney Transplant Recipients: Current Experience Andmentioning
confidence: 99%
See 1 more Smart Citation